PENGEMBANGAN MEDIA PEMBELAJARAN ALTERNATIF PHANTOM ANTENATAL CARE PADA KEGIATAN PRAKTIKUM DI LABORATORIUM KEBIDANAN - Lia, Lismiati; Hernita, Maini; Minfadlillah, Indah (NHM PRESS, 2024)
Learning in the laboratory is an important part of the overall learning process of midwifery education in order to achieve the expected graduate competencies. Many factors affect the learning process, one way to empower the potential of students is to provide a laboratory with adequate material equipment and according to needs. In the pregnancy midwifery care course, one of the competencies that students must achieve is palpation and auscultation. In this case, the available phantom is very limited and cannot provide an image for the sound of the fetal heart rate. Based on the description above, researchers are interested in developing learning media in the form of props for examining pregnant women to be used as alternative learning media in the laboratory. Hopefully, it can fulfill the ratio of tools in practicum activities and improve student skills in pregnancy examination. This study aims to develop and test antenatal care phantoms in practicum in the midwifery laboratory of the Jambi Ministry of Health Polytechnic. This research was conducted from March to September 2024. The sample in this study were 90 students and 5 lecturers and 2 education laboratory technician. The research method used is Research and Development (R&D) referring to the design developed by Borg and Gall. As for the product effectiveness test, it uses a quasi-experiment research method, with a two group pre test post test design. The statistical analysis test used Paired sample T test, Wilcoxon Signed Ranks Ranks Test and independent t test. The results of the study produced a simple pregnant woman phantom called MAMIL with the results of the expert validity trial of 3.6 (90.7%) very feasible category and field trials with a value of 3.86 (96.5%) very feasible category. The results of data analysis obtained p = 0.025 or p> 0.05 so it can be concluded that there is a significant difference in the average knowledge between non-modified phantoms and simple pregnant women phantoms (MAMIL) in antenatal care laboratory practice activities at the Department of Midwifery, Jambi Ministry of Health Polytechnic